Parents displaying family consumption in Ireland. (1st February 2022) - Kiely, Elizabeth; Ging, Debbie; Kitching, Karl; Leane, Máire
Abstract : This article considers qualitative data collected from 78 parents in an Irish study on the commercialisation and sexualisation of children. It makes a distinctive contribution in showing that the framework of family display (Finch, 2007 ) can be productively applied to the entire field of family consumption. It shows that consumption narratives can be viewed as a tool that is used to display family – in other words, showing how family is done – to internal family members and to outsiders. While family display has been more often applied empirically with non-conventional families, its relevance for all families is reasserted by our data. Our application of the family display framework shows that middle-class parenting ideals are stretched and can become unstuck when displayed by middle-class parents, the constituency most associated with their production and propagation.